Conductor ideals in Galois extensions - Prabpayak, Chanwit (Agriculture and Natural Resources, 2015)
Let K be an algebraic number field, OK its ring of integers. An order O in K is a subring of OK which contains a Z -basis for the field K. The conductor of O is the largest ideal of OK contained in O. This paper showed that Z + ƒ is the only one order in quadratic number fields having conductor ideal and conductor ideals were characterized in a Galois extension over Q.